2020
DOI: 10.1097/pq9.0000000000000322
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinating in the Emergency Department, a Novel Approach to Improve Influenza Vaccination Rates via a Quality Improvement Initiative

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…This study team found that parents decline vaccines due to uncertainty about the vaccine, a concern the child was too sick to receive the vaccine, or are unable/unwilling to wait for vaccination. 8 Similar barriers were identified during interviews with ED parents. 5 Focus groups with parents, teens, and healthcare workers characterized facilitators of vaccination.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations
“…This study team found that parents decline vaccines due to uncertainty about the vaccine, a concern the child was too sick to receive the vaccine, or are unable/unwilling to wait for vaccination. 8 Similar barriers were identified during interviews with ED parents. 5 Focus groups with parents, teens, and healthcare workers characterized facilitators of vaccination.…”
Section: Introductionmentioning
confidence: 69%
“…Stage 1 represents season 1 enhancements. 8 Season 2, stage 2A and 2B enhancements focused on facilitating communication, identifying vaccine hesitancy, reminding nurses to administer the vaccine, and adding redundancy. To facilitate communication, a “flu column” was added to the universal ED track-board.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Before the coronavirus 2019 pandemic, the PED saw increases in income-disadvantaged children who received non-urgent care [ 20 ]. Consistent with other types of prevention efforts [ 21 ] and the goal to increase equity in obesity prevention [ 22 ], the PED is a novel location to reach at-risk children without regular primary care. Furthermore, during the pandemic, technology may help reach children for obesity prevention—especially those with health disparities [ 23 ]—for referral to programs tailored to children and parents [ 24 ], as well as screening for and informing on food security resources in a manner that minimizes stigma [ 25 ].…”
Section: Introductionmentioning
confidence: 99%